REKAYASA LINGKUNGAN PEMELIHARAAN BENIH IKAN BAUNG (Hemibagrus nemurus ) UNTUK MENINGKATKAN PERTUMBUHAN DAN SINTASAN - Kusdiarti Kusdiarti; Jojo Subagja; Otong Zaenal Arifin; RR Sri Pudji Sinarni Dewi (Jurnal Akuakultur Rawa Indonesia, 2020)
Hemibagrus nemurus is a local commodity fish that is especially favored by people in South Sumatra, Java and Kalimantan. The low survival rate of H. nemurus in the seed rearing phase is one of the obstacles in developing its cultivation. In this study an environmental modification was carried out in the rearing of H. nemurus seed containers through the addition of aeration and recirculation to increase the growth and survival. The study was conducted at a hatchery of farmers in the Kemang area, West Java. The initial length of seed was 10.1 ± 0.17 mm. The container size used was 300 liters of fiberglass. Stocking density was 10 fish / L. The maintenance period was 1 month. The treatments tested were rearing of seeds in an aquarium using A) Aeration system, B) Recirculation System, and C) Aeration + Recirculation System. The results showed that the use of rearing containers equipped with Aeration + Recirculation system resulted in better growth (29.4 mm) and survival (24.5%) compared to rearing in containers with only aeration or recirculation systems. Key words : Aeration,Growth, Hemibagrus nemurus, Recirculation, Survival rate